THE REGIONAL STRUCTURE OF SWAMPY LOWLANDS: Seen From The Cultivation Of Wicker-Willows In The Right-Side Region Of Yodo River - MORITA, KEIICHI (Japanese Journal of Human Geography, 1952)
In the present study, the regional structure of marshes in a district including Ibaraki City, Tamashima Village and Tonda Town, of Mishima District, Osaka Prefecture, is examined in connection with the cultivation of wicker-willows in the rightside lowlands of Yodo River. (This report is to be linked to the author's previous report of the cultivation of nelumbo-roots.) The following conclusion is drawn tentatively from the investigation: The cultivation of wicker-willows is a necessity in the marshes along the right bank of Yodo River. There are several reasons, to wit: 1. Since the lands are low and soft, and the drainage of water is not easily carried out det to the topography of the region, it is not possible to cultivate land to grow other kinds of plants. 2. Economically advantageous conditions can be gained by the rational use of surplus labor. 3. Suitability of the geogpaphical position of the tract. 4. Human efforts to reclaim swamps in the district. On the other hand, the region is close to the large city of Osaka. Many factors as the social and the economical, which are peculiar to a suburban agrarian district which is located within the magnetic field of a metropolis, have helped to bring about the area most prominent in the cultivating of wicker-willows in this country.